TO DETERMINE EMPLOYEE ENGAGEMENT & ITS RELATIONAL OUTCOME OF BENCHMARKING MOHD AHMED KABEER - Kabeer, Mohd Ahmed; Shrivastava, Manish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The healthcare sector is facing external changes and pressure to provide high-quality treatment while benchmarking. This study outlines necessary actions for successful change management in the healthcare business using a non-intervention based observational research methodology. The study involved 336 healthcare workers from public general hospitals, private chain hospitals, specialty hospitals, and charities. Cronbach’s alpha was used to determine data reliability, with a reliability score of 0.654 for competence, 0.806 for technology, and 0.801 for engagement. The study highlights the need for effective change management in the healthcare industry.